Impact of Multiple Ecological Stressors on a Sub-Arctic Ecosystem: No Interaction Between Extreme Winter Warming Events, Nitrogen Addition and Grazing - Bokhorst, Stef; Berg, Matty P.; Edvinsen, Guro K.; Ellers, Jacintha; Heitman, Amber; Jaakola, Laura; Mæhre, Hanne K.; Phoenix, Gareth K.; Tømmervik, Hans; Bjerke, Jarle W. (Frontiers in Plant Science, 2018)
Climate change is one of many ongoing human-induced environmental changes, but few studies consider interactive effects between multiple anthropogenic disturbances. In coastal sub-arctic heathland, we quantified the impact of a factorial design simulating extreme winter warming (WW) events (7 d at 6-7 °C) combined with episodic summer nitrogen (+N) depositions (5 kg N ha-1) on plant winter physiology, plant community composition and ecosystem CO2 fluxes of an Empetrum nigrum dominated heathland during three consecutive years in northern Norway. We expected that the +N would exacerbate any stress effects caused by the WW treatment. During WW events, ecosystem respiration doubled, leaf respiration declined (-58 %), efficiency of Photosystem II (Fv/Fm) increased (between 26-88 %), while cell membrane fatty acids showed strong compositional changes as a result of the warming and freezing. In particular, longer fatty acid chains increased as a result of WW events, and eicosadienoic acid (C20:2) was lower when plants were exposed to the combination of WW and +N. A larval outbreak of geometrid moths (Epirrita autumnata and Operophtera brumata) following the first WW led to a near-complete leaf defoliation of the dominant dwarf shrubs Empetrum nigrum (-87 %) and Vaccinium myrtillus (-81 %) across all experimental plots. Leaf emergence timing, plant biomass or composition, NDVI and growing season ecosystem CO2 fluxes were unresponsive to the WW and +N treatments. The limited plant community response reflected the relative mild winter freezing temperatures (-6.6 °C to -11.8 °C) recorded after the WW events, and that the grazing pressure probably overshadowed any potential treatment effects. The grazing pressure and WW both induce damage to the evergreen shrubs and their combination should therefore be even stronger. In addition, +N could have exacerbated the impact of both extreme events, but the ecosystem responses did not support this. Therefore, our results indicate that these sub-arctic Empetrum-dominated ecosystems are highly resilient and that their responses may be limited to the event with the strongest impact.